Timor Collision Front Segmentation Reveals Potential for Great Earthquakes in the Western Outer Banda Arc, Eastern Indonesia - Coudurier-Curveur, Aurélie; Singh, Satish C.; Deighton, Ian (Frontiers in Earth Science, 2021)
In Eastern Indonesia, the western Outer Banda Arc accommodates part of the oblique Australian margin collision with Eurasia along the Timor Trough. Yet, unlike the northern Wetar and Alor thrusts and the adjacent eastern Java subduction zone, both recent and historical seismicity are extremely low. This long-term seismic quiescence questions whether the Banda Arc collision front along the Timor Trough is actually fully locked or simply aseismic, and raises major concerns on the likelihood of large magnitude and tsunamigenic earthquake occurrence in this vulnerable and densely populated region. Here, we jointly analyze multibeam bathymetry and 2D seismic reflection data acquired along the Timor Trough to characterize the location, nature, and geometry of active faults. Discontinuous narrow folds forming a young accretionary prism at the base of the Timor wedge and spatially correlated outcropping normal faults in the Australian northwest shelf reveal two concurrent (underthrusting and frontal accretion) contrasting styles of convergence accommodation. We find that the underthrusting and frontal accretion tectonic regimes depend on (1) the thickness of the incoming and underthrusting Cenozoic sedimentary sequence, (2) the vergence of inherited normal faults developed within the continental shelf, and (3) the depth of the décollement beneath the Timor wedge. Based on the along-strike, interchanging distinct deformation style, we propose a mechanical and seismic segmentation along the Banda arc collision front and discuss the implications of fluid-rich underthrusted sediments and steep frontal faults as controlling parameters for earthquake and tsunami hazards along the western Outer Banda arc region.